The Lord of the rings : the fellowship of the ring - Jackson, Peter
Follow the shy young Hobit Frodo Baggins (Elijah Wood) inherits a ring. It is one ring. An instrument to absolute power that could allow Sauron. The dark Lord of MOrdor. To rule- middle-earth and enslave its people Frodo. Together with a loyal fellowship of Hobbits, men a wizard. A Dwarf and elf must take the ring across middle-earth to the crack of doom. Where it was forged and destroy it forever together. This unlikely group of heroes travels through unfaithful lands to complete its mission. Its success or failure will decide the fate of millions and the forever.